Factors Associated with Turnover Intention Among Healthcare Workers During the Coronavirus Disease 2019 (COVID-19) Pandemic in China - Hou H; Pei Y; Yang Y; Lu L; Yan W; Gao X; Wang W (Dove Medical Press, 2021)
Hao Hou,1,* Yifei Pei,1,* Yinmei Yang,2 Lili Lu,3 Wenjun Yan,1 Xiuyin Gao,1 Wei Wang1 1Department of Community and Health Education, School of Public Health, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 2Department of Social Medicine, School of Health Sciences, Wuhan University, Wuhan, People's Republic of China; 3Department of Gastroenterology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Wang; Xiuyin GaoDepartment of Community and Health Education, School of Public Health, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of ChinaTel +86 516-83262655; +86 13813287473Email weiwang90@163.com; 460629860@qq.comPurpose: This study assessed the prevalence of turnover intention and explored associated factors on turnover intention among healthcare workers during the COVID-19 pandemic in China.Methods: An institutional-based cross-sectional study was conducted from July to February 13th to 20th, 2020, in 31 provinces of mainland China. A total of 1403 healthcare workers were recruited. Hierarchical logistic regressions were used to identify potential factors associated with turnover intention among Chinese health care workers.Results: The prevalence of turnover intention among healthcare workers was 10.1% during the COVID-19 pandemic in China. Results of hierarchical regression revealed that working in Grade II hospital (OR = 1.78), technician (OR = 0.30), daily working hours over 12 h (OR = 2.92), frequency of mask replacement between 4 and 8 h (OR = 3.51), refuse volunteer to frontline (OR = 1.68), patient-physician relation unchanged (OR = 1.73), depression (OR = 2.21) and lower social support (OR = 1.75) were significantly associated with the risk of turnover intention. Additionally, healthcare worker's psychosocial syndemic (OR = 6.13) was positively associated with turnover intention.Conclusion: Turnover intention is relatively prevalent among healthcare workers during the COVID-19 pandemic in China, and the factors contributing to turnover intention were complex and varied. Early screening of high-risk groups for turnover intention among healthcare workers and more psychosocial health care and physical protection are needed during the COVID-19 pandemic in China.Keywords: COVID-19, healthcare workers, turnover intention, China